The Analysis of English Vocabulary Learning in Lembaga Bahasa LIA Harapan Indah - Riri Rachmah Riani; Albiansyah Albiansyah; Fahriany Fahriany (International Journal of English Linguistics, Literature, and Education (IJELLE), 2020)
Abstract This research works on the using of English vocabulary learning method in Lembaga Bahasa LIA Harapan Indah. The aims of this research are to investigate the English vocabulary learning method, which is used in young learner and adult learner classes. This research is qualitative research and using ethnography fieldwork research. Observation, interview, and questionnaire are used as a method to collect the data. The result of this research shows that there are three English vocabulary learning methods which are used by Lembaga Bahasa LIA Harapan Indah. Those are direct method, total physical response (TPR), and games. Keywords: Vocabulary learning, English vocabulary teaching method